Respostas

  • Usuário do Brainly
2014-08-21T00:32:50-03:00
A)
(3x-1)² + (x-2)²=

9x²-6x+1+x²-4x+4=
10x²-10x+5

b)
(a³-2)²-(a³+1)²=

  a^{6} -4 a^{3} +4-( a^{6} +2 a^{3} +1)=

 a^{6} -4 a^{3} +4- a^{6} -2 a^{3} -1=

-6a³+3

c)
(1-2x)²-(1+x)²=

1-4x+4x²-(1+2x+x²)=
1-4x+4x²-1-2x-x²=

3x²-6x
2 4 2
A melhor resposta!
  • Usuário do Brainly
2014-08-21T18:26:51-03:00
A) (3x-1)^2+(x-2)^2

Em geral, (a+b)=a^2+2ab+b^2 e (a-b)^2=a^2-2ab+b^2.

Assim:

\rhd (3x-1)^2=(3x)^2-2\cdot 3x\cdot 1+1^2=9x^2-6x+1

\rhd (x-2)^2=x^2-2\cdot x\cdot 2+2^2=x^2-4x+4

Portanto, :

(3x-1)^2+(x-2)^2=(9x^2-6x+1)+(x^2-4x+4)=10x^2-10x+5.

b) De modo análogo, obtemos:

\bullet (a^3-2)^2=(a^3)^2-2\cdot a^3\cdot 2+2^2=a^6-4a^3+4

\bullet (a^3+1)^2=(a^3)^2+2\cdot a^3\cdot1+1^2=a^6+2a^3+1

Logo, :

(a^3-2)^2-(a^3+1)^2=(a^6-4a^3+4)-(a^6+2a^3+1)=-6a^3+3

c) Por fim, temos:

\rhd (1-2x)^2=1^2-2\cdot 1\cdot 2x+(2x)^2=1-4x+4x^2

\rhd (1+x)^2=1^2+2\cdot1\cdot x+x^2=1+2x+x^2

E obtemos, :

(1-2x)^2-(1+x)^2=(1-4x+4x^2)-(1+2x+x^2)=3x^2-6x
2 5 2